2021
DOI: 10.3390/membranes11020111
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effect of Cannabidiol on the Composition and Physicochemical Properties of Keratinocyte and Fibroblast Membranes from Psoriatic Patients and Healthy People

Abstract: The development of psoriasis is accompanied by oxidative stress, which can modify the components of skin cells. Therefore, the aim of this study was to evaluate the effect of cannabidiol (CBD), an antioxidant and anti-inflammatory phytocannabinoid, on the composition and physicochemical properties of the membranes of healthy and psoriatic keratinocytes and fibroblasts exposed to ultraviolet A (UVA) and ultraviolet B (UVB) radiation. In psoriasis-altered cells, decreased levels of the main groups of phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Similarly, previous studies have demonstrated beneficial anti-aging effects on fibroblasts with the use of cannabis extracts which included phytocannabinoids; however, pure THC and CBD were not tested, and the compounds that induce these anti-aging effects were not identified [ 18 , 19 , 20 , 21 ]. In addition, some studies have shown CBD exposure on dermal fibroblasts prevented structural changes caused by psoriasis [ 22 ] and ameliorated proteome changes after UV damage [ 23 ]. There, however, remains a lack of knowledge on the anti-aging and rejuvenation effects of THC and CBD on healthy and aged human dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, previous studies have demonstrated beneficial anti-aging effects on fibroblasts with the use of cannabis extracts which included phytocannabinoids; however, pure THC and CBD were not tested, and the compounds that induce these anti-aging effects were not identified [ 18 , 19 , 20 , 21 ]. In addition, some studies have shown CBD exposure on dermal fibroblasts prevented structural changes caused by psoriasis [ 22 ] and ameliorated proteome changes after UV damage [ 23 ]. There, however, remains a lack of knowledge on the anti-aging and rejuvenation effects of THC and CBD on healthy and aged human dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…We recently documented that increased levels of lipid peroxidation products in the epidermis results from smoking [ 6 ] or obesity [ 7 ]. Additionally, direct skin exposure to pro-oxidants, such as ultraviolet UVA and UVB radiation, enhanced oxidative damage of membrane lipids in both normal and psoriatic keratinocytes and fibroblasts [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 16 , 17 Accordingly, peripheral application of cannabinoid‐related compounds has shown therapeutic benefits, decreasing associated comorbidities and reconstituting proper skin tissue architecture and physiology. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…13,16,17 Accordingly, peripheral application of cannabinoid-related compounds has shown therapeutic benefits, decreasing associated comorbidities and reconstituting proper skin tissue architecture and physiology. 18,19 These CBR-based treatments recently have attracted considerable attention in equine veterinary medicine after their use in other vertebrate species, including dogs, cats, and pigs. [20][21][22][23][24] Unfortunately, knowledge about the ECS in horses is still limited to dorsal root ganglion (DRG) neurons and equine genome sequencing analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation